1999
DOI: 10.1097/00005392-199901000-00027
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Upper Tract Cytology After Transurethral Resection of Bladder Tumor in Patients With Bladder Transitional Cell Cancer

Abstract: Given the normal appearance of the upper urinary tract, it is highly unlikely that most, if any, of these patients with bladder cancer have tumor in the upper tract despite tumor cells in urine obtained by retrograde catheterization. Thus, upper tract sampling by a retrograde technique lacks specificity for localizing transitional cell cancer to the upper tract when performed in a patient with bladder cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Notably, two of the present patients required additional treatment for upper tract recurrences. While the proportion of patients diagnosed with NMIBC who go on to develop upper tract TCC is traditionally considered to be <3%[23–25], patients with high‐risk superficial disease have been reported to have upper tract recurrence rates of up to 18% after BCG treatment [26,27]. It is difficult to make any inferences without a randomized controlled trial as to whether treatment with intravesical docetaxel positively or negatively altered the risk of upper tract recurrence in the present patients, who were already at increased risk from previous BCG treatment, but our observation indicates the necessity of close surveillance of the upper tract in patients having bladder recurrences after BCG therapy.…”
Section: Discussionmentioning
confidence: 60%
“…Notably, two of the present patients required additional treatment for upper tract recurrences. While the proportion of patients diagnosed with NMIBC who go on to develop upper tract TCC is traditionally considered to be <3%[23–25], patients with high‐risk superficial disease have been reported to have upper tract recurrence rates of up to 18% after BCG treatment [26,27]. It is difficult to make any inferences without a randomized controlled trial as to whether treatment with intravesical docetaxel positively or negatively altered the risk of upper tract recurrence in the present patients, who were already at increased risk from previous BCG treatment, but our observation indicates the necessity of close surveillance of the upper tract in patients having bladder recurrences after BCG therapy.…”
Section: Discussionmentioning
confidence: 60%
“…Intraoperative upper tract urine cytology examination might increase the cost, lengthen the operating period and cause urinary tract infection. To our knowledge, only one study has reported the value of upper tract urine cytology examination at the same time as TUR; that study concluded that sampling of urine from the upper tract was not accurate because of contamination . However, the number of patients was very small; in addition, the patients were diagnosed as having “no malignancy” because of normal upper tract appearance on radiography.…”
mentioning
confidence: 99%